Fuel Cell Electric Vehicle Technology - Wei, Junyan (International Journal of Mechanical and Electrical Engineering, 2024)
Nowadays, the level of science and technology is developing rapidly, and there are more and more ways for people to choose to travel. Under the environment of people’s increasing pursuit of environmental protection and sustainable development, the development of the electric vehicle industry has attracted much attention, which contains fuel cell electric vehicles. Fuel cell electric vehicles, as one of the many types of electric vehicles, are special in that chemical energy is converted into electrical energy through the reaction of hydrogen and oxygen, and then the electrical energy is converted into mechanical energy through the drive system. This paper describes the types of fuel cell electric vehicles, introduces the working principle and basic mechanism in detail, and explores the development prospects of the related industry and the basic problems faced by it through the study of its core technology, so as to provide some references for the development of new energy automobile related industries.